Self-regulated learning of primary school teachers, reviewed from external factors: Self regulated learning guru sekolah dasar, ditinjau dari faktor eksternal - Fasti Rola (Talenta Publisher, 2023)
This study aims to examine the overview and differences in self-regulated learning among elementary school teachers in terms of external factors such as teacher income, job position, and school status. The participants were 72 primary and junior high school teachers from North Sumatra recruited using an incidental sampling method. The measuring instrument employed is a self-regulating learning scale set up by the characteristics indicated by Pintrich, Smith, Garcia, and McKeachie (1991). The results show that self-regulated learning instructors are in the top group, and there is no difference in self-regulated learning teachers in terms of salary, work position, or school status.